A method for preparing and applying a self-leveling filler for abandoned pipeline materials

By preparing a self-leveling filling material for waste pipes, the treatment problem caused by the high water content and high viscosity of waste sludge from water purification was solved, realizing resource utilization and environmentally friendly pipe filling, and reducing costs and land occupation risks.

CN120117855BActive Publication Date: 2025-11-18GUANGZHOU WATER SUPPLY CO +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510278133.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-11-18
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

The high moisture content and high viscosity of the residual sludge from water purification make it difficult to treat. Existing treatment methods consume resources and space and pose environmental risks.

Method used

A method for preparing self-leveling filler for abandoned pipes involves mixing composite powder and de-adhesive solution with clean water and residual mud to form a fluidized and solidified residual mud slurry. After vibration and tamping using a cement mortar vibrating table, the slurry is demolded and used for filling underground abandoned pipes.

Benefits of technology

It realizes the resource utilization of waste sludge from water purification, reduces treatment costs, improves fluidity and solidification effect, avoids landfill and environmental risks, and has good green and environmental protection benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120117855B_ABST
    Figure CN120117855B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and particularly discloses a preparation method and application of a self-leveling filling waste pipeline material, which comprises the following steps: obtaining clean water residual mud generated by sewage treatment of a pure device, mixing a debonding agent solution into the clean water residual mud in a stirring pot, and stirring the clean water residual mud by using a mortar planetary mixer to obtain a clean water residual mud slurry; configuring a composite powder by using a cement powder and a slag powder, mixing the composite powder into the clean water residual mud slurry, and mixing the clean water residual mud slurry uniformly by using a planetary mixer for a first preset time to form a flowable solidified residual mud slurry; storing the flowable solidified residual mud slurry in a column mold, vibrating the flowable solidified residual mud slurry on a cement mortar vibrating table for a second preset time, and then demolding to obtain a solidified residual mud filling material; and the application has the following advantages: the flow effect before solidification is improved through the resource utilization of the slag powder and the cement solidification cooperation; the clean water residual mud is used as a main filling material, and the application has the advantages of low production cost, large output, small pollution and good flow solidification effect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a preparation method and application of a self-leveling filling waste pipeline material. BACKGROUND

[0002] With the continuous advancement of urbanization, people's living standards continue to improve, and the supporting requirements for public infrastructure are also increasing. Various pure equipment for sewage treatment (such as membrane separation devices, high-efficiency filtration units, etc.) are being applied on a larger scale in cities, and the amount of associated solid waste, i.e., clean water residual mud, is also increasing year by year. Some pure equipment operators in a city revealed that the daily disposal of clean water residual mud has reached hundreds of tons, and the output is considerable.

[0003] However, these clean water residual muds face many difficulties in treatment and subsequent disposal: they usually have high water content, high compressibility, high aggregate content, and high viscosity, etc. Unfavorable engineering properties, resulting in high difficulty in drying or dewatering, inconvenience in transportation, and difficulty in management during stacking and landfill. At the same time, since the clean water residual mud is derived from the water filtration and purification process, various impurities and flocculants together form a relatively complex muddy or gel-like material, which is difficult to achieve effective reduction and resource utilization under conventional treatment methods. The existing treatment methods are mainly temporary filling, stacking or burying, which not only occupies valuable land and space resources, but also poses certain environmental risks.

[0004] Therefore, how to effectively reduce, stabilize and resource the clean water residual mud generated by the pure equipment for sewage treatment while taking into account the economy and environmental protection has become an important issue to be solved in the process of sustainable urban development.

[0005] Therefore, a preparation method and application of a self-leveling filling waste pipeline material are proposed to solve the above problems. SUMMARY

[0006] The present application aims to provide a preparation method and application of a self-leveling filling waste pipeline material to solve or improve the above technical problems of high water content and high viscosity of clean water residual mud, which leads to high difficulty in treatment, and the existing treatment methods occupy resources and space.

[0007] Therefore, the first aspect of the present application is to provide a preparation method of a self-leveling filling waste pipeline material.

[0008] The second aspect of the present application is to provide a self-leveling filling waste pipeline material.

[0009] The third aspect of the present application is to provide an application of a self-leveling filling waste pipeline material.

[0010] The first aspect of the present application provides a preparation method of a self-leveling filling waste pipeline material, comprising the following steps: obtaining clean water residual mud generated by a clean device treating sewage, configuring the total mass of the composite powder and the total mass of the debonding agent solution based on the total mass of the clean water residual mud; mixing the debonding agent solution into the clean water residual mud in a stirring pot, stirring to obtain a clean water residual mud slurry body by using a mortar planetary mixer; configuring the composite powder by using cement powder and slag powder, mixing the composite powder into the clean water residual mud slurry body and mixing uniformly for a first preset time by using a planetary mixer to form a flowable solidified residual mud slurry body; storing the flowable solidified residual mud slurry body in a columnar mold, demolding to obtain a solidified residual mud filling material after vibration by using a cement mortar vibration table for a second preset time.

[0011] The second aspect of the present application provides a self-leveling filling waste pipeline material, raw materials of which include a composite powder, a debonding agent solution and clean water residual mud; the clean water residual mud is in a high-viscosity mud body state, and the composition of the clean water residual mud includes at least one of silicon dioxide, aluminum oxide, iron oxide, potassium oxide, titanium dioxide, diaphosphorus pentoxide, magnesium oxide and calcium oxide; the mass ratio of the composite powder to the clean water residual mud is 0.20-0.30; and the mass ratio of the debonding agent solution to the clean water residual mud is 0.17-0.19.

[0012] The third aspect of the present application provides an application of a self-leveling filling waste pipeline material, comprising the following steps: placing a stirring barrel on the ground and excavating earthwork above a to-be-treated underground waste pipeline to form a through grouting hole; connecting the stirring barrel, a grouting pump and a grouting hole of the underground waste pipeline through a grout conveying pipe; stirring and mixing the composite powder, the debonding agent solution and the clean water residual mud in the stirring barrel to obtain the flowable solidified residual mud slurry body; pumping the flowable solidified residual mud slurry body into the underground waste pipeline through the grouting pump and the grout conveying pipe, and repeatedly pumping until the filling of the slurry body in the waste pipeline is completed.

[0013] Compared with the prior art, the present application has the following beneficial effects:

[0014] The process of the present application is simple and convenient, has low energy consumption, is widely applicable, and has good green environmental protection benefits and social safety benefits.

[0015] The present application utilizes slag powder solid waste as a resource, provides a solution to the problem of large quantity and high processing cost, and uses industrialized cement products with high maturity as raw materials, which are supplemented by slag powder for collaborative solidification, thereby improving the solidification effect and being conducive to the development of waste resource economy.

[0016] This invention uses readily available sodium citrate as a deviscosifying agent, effectively solving the problem of high viscosity in waste sludge from water purification, allowing the waste sludge to have high fluidity without complex processing.

[0017] This invention uses the residual sludge from water treatment plant production as the main agent of the self-leveling filler material. Compared with the commonly used foamed concrete filler materials, it has the advantages of low production cost, large output, and low pollution, and does not require the addition of additional additives, and has good flow and curing effect.

[0018] Additional aspects and advantages of embodiments of the invention will become apparent in the following description or may be learned by practice of embodiments of the invention. Attached Figure Description

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0020] Fig. 1 This is a flowchart of the preparation method of the present invention;

[0021] Fig. 2 This is a flowchart of the method steps for applying the present invention;

[0022] Fig. 3 This is a schematic diagram illustrating the grouting construction application of the present invention. Detailed Implementation

[0023] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.

[0024] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0025] Please see Figs. 1-3 The following describes a method for preparing and applying a self-leveling filler material for waste pipes, according to some embodiments of the present invention.

[0026] An embodiment of the first aspect of the present invention provides a self-leveling filling material for waste pipes. In some embodiments of the present invention, the raw materials for the self-leveling filling material for waste pipes include composite powder, descaling agent solution, and purified sludge; the purified sludge is in the state of a highly viscous slurry, and the components of the purified sludge include at least one selected from silicon dioxide, aluminum oxide, iron oxide, potassium oxide, titanium dioxide, phosphorus pentoxide, magnesium oxide, and calcium oxide.

[0027] The mass ratio of composite powder to residual sludge from water purification is between 0.20 and 0.30.

[0028] The mass ratio of the descaling agent solution to the residual sludge in the purified water is between 0.17 and 0.19.

[0029] This invention provides a self-leveling filling material for waste pipes. The composite powder is a key component added to improve the solidification ability of waste sludge. Waste sludge itself has high water content and high viscosity, making it difficult to handle directly and potentially affecting its filling effect. The interaction of the composite curing agent and the sludge itself creates a more robust structure. Its curing process helps improve the stability of the material within the pipe, preventing premature loss of fluidity or excessive expansion. For example, gypsum, calcium chloride, and calcium aluminate can be used as components of the composite powder. The mass ratio of the composite powder to the waste sludge is 0.20 to 0.30, ensuring that the curing reaction does not occur too quickly, allowing sufficient time to complete the filling process, while avoiding cracks and splitting caused by excessive drying.

[0030] De-viscosifying solution is an important component used to reduce the high viscosity of wastewater treatment sludge. Because wastewater treatment sludge forms highly viscous agglomerates during water treatment, direct use as filler can lead to excessive viscosity, affecting the material's flowability and self-leveling properties. De-viscosifying solution reduces this viscosity, enhances sludge flowability, and ensures the material can be evenly distributed and self-leveled within the waste pipe. The addition of this solution effectively reduces clogging problems and ensures ease of application during the filling process. De-viscosifying solution can be made from certain surfactants, dilute acids, or water-soluble polymers. The mass ratio of de-viscosifying solution is set between 0.17 and 0.19 of the wastewater treatment sludge to ensure the de-viscosifying agent functions effectively, avoiding excessive or insufficient use, and ensuring optimal material flowability and workability.

[0031] By rationally controlling the mass ratio of the composite curing agent to the residual sludge from the treated water system, the curing process of the filling material within the pipeline can be made more stable. An excessively high proportion of the composite curing agent may cause the material to cure too quickly, thus affecting the filling effect; while an excessively low proportion may result in ineffective curing, affecting the performance of the flowable residual sludge. Therefore, setting the ratio between 0.20 and 0.30 optimizes the curing speed and performance while ensuring the filling effect. Setting the ratio of the de-adhesive solution to the residual sludge between 0.17 and 0.19 ensures that the viscosity of the residual sludge is reduced without affecting its filling characteristics. The use of the de-adhesive solution allows the highly viscous slurry to flow more smoothly into the waste pipeline and form a uniform filling layer within the pipeline. By rationally adjusting the proportion of the de-adhesive, the slurry can be prevented from becoming too thin, thus avoiding negative impacts on the filling effect.

[0032] In any of the above embodiments, the composite powder includes cement powder and slag powder, and the mass ratio of slag powder to cement powder is between 0.1 and 1.

[0033] In this embodiment, cement powder is one of the main components of the composite powder, possessing very strong curing ability. The basic components of cement include calcium oxide (CaO), which reacts with water to form calcium hydroxide (Ca(OH)2), further reacting with other components to generate mineral compounds such as calcium silicate and calcium aluminate. These compounds provide a robust structural foundation during the cement hardening process. Therefore, the addition of cement powder can improve the curing efficiency of the composite curing agent, ensuring that the filler material can firmly bond after being filled into the pipe, forming a filling layer with high mechanical strength. Commonly used types of cement powder include ordinary Portland cement, slag cement, or other special cements. A higher mass proportion of cement powder helps accelerate the cement hydration reaction, achieving high-strength curing in a short time, suitable for scenarios requiring rapid filling and sealing.

[0034] Slag powder is an industrial byproduct, primarily composed of minerals such as silicon dioxide (SiO2), calcium oxide (CaO), and aluminum oxide (Al2O3). The addition of slag powder improves the hydration process of cement powder, resulting in a slower and more stable cement reaction, reducing the adverse effects of excessively rapid hardening. When slag powder and cement powder work together, compounds such as calcium silicate and calcium aluminate are formed. These compounds contribute to enhancing the material's durability, impermeability, and chemical corrosion resistance during later hardening processes. Therefore, slag powder not only improves the overall performance of the material but also enhances its environmental friendliness, making it more aligned with sustainable development requirements. Common slag powders include blast furnace slag powder. As a waste resource, the addition of slag powder effectively utilizes industrial waste, reduces the overall cost of the material, and improves its durability. In practical applications, the proportion of slag powder can be adjusted according to different hardening requirements and environmental conditions.

[0035] It should be clarified that the composite curing agent can interact with each other, utilizing the synergistic effect of the alkalinity of cement and the activity of slag powder to solidify the residual sludge after water purification. Furthermore, due to the addition of slag powder, slag powder is inserted between the cement and residual sludge particles, reducing their hydration rate and prolonging the time that the residual sludge retains its fluidity after the addition of the composite curing agent.

[0036] In any of the above embodiments, the slag powder comprises at least one of calcium oxide, silicon dioxide, sulfur trioxide, aluminum oxide, iron oxide, magnesium oxide, sodium oxide, and potassium oxide.

[0037] In this embodiment, the filling requirements for abandoned pipes need to balance rapid curing and long-term stability. In this case, the following slag powder composition ratio can be selected: 30% calcium oxide (CaO), 25% silicon dioxide (SiO2), 5% sulfur trioxide (SO3), 15% aluminum oxide (Al2O3), 10% iron oxide (Fe2O3), 5% magnesium oxide (MgO), and a combined 10% sodium oxide (Na2O) and potassium oxide (K2O). This ratio ensures that the filling material has good flowability and a suitable curing speed in the initial stage, while exhibiting stronger durability and impermeability in the later stage, avoiding the adverse consequences of excessive amounts of certain components in the slag powder.

[0038] In any of the above embodiments, the cement powder comprises at least one of calcium oxide, silicon dioxide, aluminum oxide, iron oxide, magnesium oxide, sulfur trioxide, potassium oxide, and titanium dioxide.

[0039] In this embodiment, taking the filling of waste pipes as an example, the composition ratio of cement powder can be optimized as follows, depending on the requirements: Calcium oxide (CaO): 40%–50%, Silicon dioxide (SiO2): 25%–30%, Alumina (Al2O3): 10%–15%, Iron oxide (Fe2O3): 5%–10%, Magnesium oxide (MgO): 2%–5%, Sulfur trioxide (SO3): 2%–4%, Potassium oxide (K2O): 0%–2%, Titanium dioxide (TiO2): appropriate amount (depending on requirements). If the filling pipe requires high strength and impermeability, the proportion of silicon dioxide and alumina can be appropriately increased, such as silicon dioxide content of 30% and alumina content of 15%, while reducing the proportion of potassium oxide to below 1%. This not only ensures higher long-term durability of the filling material but also prevents expansion problems. For scenarios requiring rapid repair and filling, the proportion of calcium oxide can be increased to around 50%, while the content of silica and alumina can be reduced, thereby accelerating the reaction speed of the cement to meet the needs of rapid curing.

[0040] In any of the above embodiments, the desiccant solution includes a sodium citrate solution; the sodium citrate in the sodium citrate solution accounts for 6 to 12 parts by mass, and the water in the sodium citrate solution accounts for 88 to 94 parts by mass.

[0041] In this embodiment, the sodium citrate solution is pretreated before use by heating it to a certain temperature (e.g., 50°C) to make it easier to dissolve and better penetrate into the highly viscous areas of residual sludge in the purified water, thereby reducing the required amount of desiccant and achieving good results.

[0042] A second aspect of the present invention provides a method for preparing a self-leveling filling material for waste pipes as described in any of the above embodiments. In some embodiments of the present invention, such as... Fig. 1As shown, the preparation method includes the following steps:

[0043] S101, based on the total mass of the composite powder, take 0-33.3 parts by weight of slag powder and 33.3-66.7 parts by weight of cement, and mix them initially under normal temperature and dry conditions to obtain composite curing agent powder.

[0044] S102, based on the total mass of the de-adhesive solution, take 6-12 parts by weight of sodium citrate and 88-94 parts by weight of water, dissolve sodium citrate in water to prepare a de-adhesive solution, mix it with the clean water and residual mud in the mixing pot, and use a mortar planetary mixer to stir to obtain clean water and residual mud slurry.

[0045] S103, the composite powder is prepared by mixing cement powder and slag powder, the composite powder is added to the purified water residue slurry and a planetary mixer is used to perform mixing for a first preset time to form a fluid solidified residue slurry.

[0046] S104, the flowable solidified residual mud slurry is stored in the column mold, and after vibrating and tamping on the cement mortar vibrating table for a second preset time, the solidified residual mud filling material is obtained by demolding.

[0047] This invention proposes a preparation method. Step S101 aims to prepare a composite curing agent powder, which serves as an important component of a self-leveling filling material for waste pipes. This is achieved by mixing slag powder and cement powder to obtain a powder material with good curing properties. In this step, the mass ratio of slag powder to cement powder is adjusted by controlling the amount of slag powder added and the proportion of cement (0–33.3 parts by weight of slag powder, 33.3–66.7 parts by weight of cement) to adjust the properties of the curing agent and ensure the material's strength, flowability, and self-leveling characteristics. Assuming the mass of slag powder is 20 parts by weight and the mass of cement is 50 parts by weight (within this range), the two powders are first roughly mixed under room temperature and drying conditions, and then further finely mixed using a stirrer to ensure uniform distribution, providing stability and uniformity for the subsequent use of the composite curing agent powder. By precisely controlling the ratio of slag powder to cement powder, the hardness, drying time, and durability of the final curing agent can be adjusted. The introduction of slag powder can improve the compressive strength of cement and reduce costs, while the addition of cement can provide good adhesion and stability to the curing system. Optimizing this mixing ratio and process is key to ensuring that the subsequent self-leveling filler can be successfully molded and possess good performance.

[0048] In step S102, the preparation of the de-adhesive solution aims to address the high viscosity problem of residual sludge from water treatment. By mixing sodium citrate with water to form a solution, the viscosity of the sludge can be effectively reduced, its fluidity improved, and adhesion or clogging avoided during subsequent mixing. The addition of the de-adhesive solution makes it easier for the residual sludge to be fully mixed with the composite powder during mixing. The selected amounts are 8 parts by weight of sodium citrate and 92 parts by weight of water (meeting the required ratio of 6-12 parts by weight and 88-94 parts by weight). First, sodium citrate is added to water and completely dissolved under stirring to form a clear de-adhesive solution. This solution has strong solubility and can quickly penetrate the high-viscosity areas of the residual sludge, resulting in lower adhesion and facilitating subsequent operations. As a de-adhesive, sodium citrate effectively breaks down the viscous structure in the residual sludge, promoting sludge fluidity and making subsequent mixing smoother. Furthermore, the water solubility of the solution also helps reduce the negative impact of the de-adhesive on the material itself, ensuring the stability and uniformity of the material during construction. A proper ratio of sodium citrate to water ensures the durability and effectiveness of the degreasing effect.

[0049] In step S103, the composite curing agent powder and the purified water residue slurry are mixed to fully combine them and form a highly fluid cured residue slurry. The planetary mixer is used again for mixing to ensure a uniform distribution between the composite curing agent powder and the purified water residue slurry, resulting in a final fluid cured residue slurry that possesses sufficient fluidity while maintaining good stability and strength after curing. During the mixing process, the prepared composite curing agent powder (e.g., 20 parts by weight of slag powder and 50 parts by weight of cement powder) is added to the already uniformly mixed purified water residue slurry. The planetary mixer is used for thorough mixing, and repeated mixing ensures complete integration of the composite curing agent powder and the slurry. At this point, the slurry exhibits good fluidity and can effectively fill the voids in the waste pipe. This mixing process not only ensures the uniform integration of the curing agent and the slurry but also, through the efficient mixing function of the planetary mixer, ensures optimal interaction between the curing agent powder and the purified water residue slurry, avoiding inconsistencies in physical properties due to uneven mixing. This mixed, flowable, solidified slurry has good workability, can easily fill the gaps in the pipe, and forms a stable repair effect after solidification.

[0050] In step S104, the solidified slurry is thoroughly mixed and then placed in a column mold for vibratory compaction. Vibratory compaction removes air bubbles from the material through mechanical vibration, making the material more compact and preventing voids or cracks after curing. After demolding, the solidified slurry forms a strong and stable solidified object, achieving the curing of the water purification slurry. The well-mixed solidified slurry is poured into the column mold, the mold size of which is selected according to the actual needs of the filling pipe. A cement mortar vibrating table is used to vibrate and compact the mold, ensuring the slurry is evenly distributed within the mold and removing excess air bubbles. After a period of vibratory compaction, the mold is demolded, yielding the cured solidified slurry. Vibratory compaction not only enhances the density of the solidified slurry but also ensures that the final shape of the material meets engineering requirements. By removing air bubbles, voids or cracks are avoided after curing, improving the compressive strength and durability of the material.

[0051] It is important to clarify that the cured residue after demolding is experimental material, used for tests such as compressive strength testing, to determine if the current component ratio meets the performance requirements. The composite curing agent powder and the purified water residue slurry must be thoroughly mixed and injected into the pipeline in a fluid state to achieve the purpose of filling the pipeline.

[0052] Specifically, the total mass of the composite curing agent powder and the total mass of the de-adhesive solution are set based on the mass of the residual sludge after water purification.

[0053] As mentioned above, the total mass of the composite curing agent powder can be dynamically adjusted proportionally based on the mass of the purified sludge, but should be determined according to the moisture content and viscosity characteristics of the purified sludge. For example, for purified sludge with a high moisture content, the proportion of the composite curing agent powder can be appropriately reduced to avoid excessive curing agent causing the slurry to become too hard and lose its good fluidity and self-leveling properties. On the other hand, for purified sludge with high viscosity and high agglomeration, the amount of curing agent can be appropriately increased to ensure a good curing effect.

[0054] The total mass of the de-adhesive solution should also be dynamically adjusted according to the viscosity of the purified sludge. For highly viscous purified sludge that is difficult to stir, the proportion of the de-adhesive solution can be appropriately increased to reduce the viscosity of the sludge and ensure the smooth progress of subsequent stirring processes. At the same time, the proportion of sodium citrate in the de-adhesive solution can also be fine-tuned according to the acidity, alkalinity, and viscosity characteristics of the purified sludge to achieve the best de-adhesion effect while avoiding excessive use of sodium citrate, which would lead to excessive costs.

[0055] Specifically, the composite powder is used to maintain the fluidity of the residual sludge after it has been solidified.

[0056] As mentioned above, the main components of the composite powder include cement powder and slag powder, but a certain proportion of high-efficiency fluidizing agent can be added to enhance its fluidity. The addition of the fluidizing agent helps reduce the viscosity of the slurry during the solidification process, maintaining its good fluidity and preventing premature solidification or clumping. These fluidizing agents can be inorganic salts or organic polymers, which can synergistically interact with the cement powder and slag powder during the solidification process, ensuring that the slurry retains a certain degree of fluidity after solidification, thus guaranteeing the smooth progress of subsequent construction operations.

[0057] Regarding the particle size of the composite powder, micronization can refine the particle size of slag powder and cement powder to a certain range, especially optimizing the specific surface area. This increases the contact area between the powder and cement paste and residual sludge, thereby improving the reaction rate and fluidity during the curing process. Furthermore, considering the potential gelation during curing, the surface of the composite powder particles can be specially treated, such as by coating a thin waterproof or anti-adhesion coating, to reduce the adhesion between cement and slag particles and further enhance the fluidity of the slurry.

[0058] During the solidification process, the amount of composite powder added should not only consider the characteristics of the purified sludge but also be adjusted appropriately based on real-time feedback on the slurry's fluidity. For example, an intelligent control system can be designed to adjust the amount of composite powder added in real time based on viscosity changes during mixing. When the slurry hardens prematurely or its viscosity is too high, the system automatically increases the amount of fluidizing agent added; conversely, when the fluidity is too strong, the proportion of fluidizing agent is appropriately reduced to maintain stable fluidity of the slurry. This feedback-based fluidity adjustment mechanism enables precise control during production, avoids unnecessary waste, and ensures the quality of the final product and construction efficiency.

[0059] To ensure that the cured residual sludge maintains sufficient fluidity while forming a stable structure after curing, a slow-release curing agent can be introduced into the composite powder. These slow-release curing agents release reactants slowly during the curing process, slowing down the curing reaction and thus maintaining the fluidity of the sludge for a longer period, reducing the risk of premature setting or mold clogging. This method not only improves production flexibility but also ensures the integrity and quality of the finished product.

[0060] Furthermore, before the cement powder comes into contact with the clean water residue slurry, the slag powder is mixed with the cement powder to form an isolation layer between the cement powder particles. This isolation layer inhibits the hydration reaction of the cement, thereby maintaining long-distance and long-term fluidity within the pipeline.

[0061] As described above, before the cement powder comes into contact with the purified sludge slurry, the slag powder and cement powder are first thoroughly mixed to ensure that the slag powder is evenly filled and distributed between the cement powder particles, forming a homogeneous and continuous isolation layer structure. Due to the fine particle size of the slag powder, it has a strong physical filling effect, effectively increasing the gaps between cement powder particles, reducing the probability of contact between particles, and significantly delaying the contact and reaction between the cement powder and the free water in the purified sludge. Therefore, the isolation layer formed by the slag powder can effectively inhibit the early rapid hydration reaction of the cement powder and slow down the formation rate of initial gel products (such as calcium hydroxide and CSH gel) in the system, thereby maintaining the fluidity of the mixed slurry for a longer period. This measure allows the solidified material to maintain better pumpability and workability during pipeline transportation, enabling long-distance transportation of the slurry and effectively preventing blockage caused by premature solidification of the mixed slurry during transportation, greatly improving the flexibility and economy of the construction process. Furthermore, the physical isolation between slag powder and cement powder particles can be gradually weakened in the later stages of the system, allowing the slag powder to gradually participate in the secondary hydration reaction (Poisson reaction) in synergy with the cement powder, thereby further improving the strength, structural density, and impermeability durability of the final solidified material, and achieving efficient resource-based disposal of clean water and residual sludge.

[0062] Furthermore, the composite powder is used to maintain the fluidity of the purified sludge slurry after solidification; and the first preset time is set according to the mass ratio of slag powder to cement powder. The first preset time is used to adjust the mixing time to ensure that the cement hydration reaction time is adjusted under the same mass ratio, and can be adapted to the internal flow length of pipes of different lengths and the flow time affected by bends, pipe diameters and inner wall roughness, so that the mixed mixture can solidify in the correct position after flow.

[0063] As mentioned above, by using a reasonable ratio of slag powder and cement powder, the composite powder can effectively control the fluidity retention time of the purified sludge slurry before solidification, thus meeting the needs of different construction environments. Specifically, the mass ratio of slag powder to cement powder in the composite powder directly determines the rate of cement hydration reaction in the mixed slurry, thereby affecting the duration of fluidity retention. Therefore, in actual engineering implementation, a reasonable first preset time can be determined and set in advance based on parameters such as the length, diameter, curvature, and inner wall roughness of the pipeline, to precisely adjust the on-site mixing time of the slurry.

[0064] For example, when the conveying distance is long (e.g., 800 to 1000 meters), the inner wall of the pipe is rough, there are multiple bends, and the pipe diameter is small, the upper limit of the mass ratio of slag powder to cement powder can be selected, which is approximately 0.8. The first preset time is set to 30 minutes to ensure that the slurry remains in a flowing state for a long time during the conveying process, effectively preventing the slurry from clogging the pipe or failing to reach the designated location due to premature solidification. Conversely, for construction environments with shorter pipe lengths (e.g., 100 to 200 meters), larger pipe diameters, fewer bends, and smoother inner walls, the lower limit of the mass ratio of slag powder to cement powder can be selected, which is 0.3. The first preset time is set to 15 minutes to ensure that the slurry can be quickly conveyed to the target location and solidified in time, avoiding the reduction in project efficiency due to the slurry not solidifying for a long time.

[0065] Furthermore, the deviscosifying solution is used to remove the high viscosity of the residual sludge from the clean water and improve the fluidity of the solidified residual sludge; and the second preset time is set according to the current filling length of the waste pipe. The second preset time can be used to determine in advance whether the solidified residual sludge can be in a state between fluidity and solidification at the current time, so as to determine whether the solidified residual sludge under this condition is qualified.

[0066] As mentioned above, the de-adhesive solution is mainly used in actual construction to significantly reduce the high viscosity of the residual sludge from water purification, thereby improving the overall fluidity of the sludge after mixing with the composite powder. This facilitates smooth and stable long-distance transportation of the sludge in abandoned pipelines and ensures accurate solidification. Specifically, after being added, the de-adhesive solution can quickly and effectively destroy the agglomerate structure present in the residual sludge from water purification, fully dispersing the particles in the sludge, rapidly reducing viscosity, and significantly improving overall fluidity.

[0067] Meanwhile, to accurately assess the flow and solidification properties of the slurry during pipeline filling and transportation, a second preset time can be set based on the current length of the abandoned pipeline. This allows for real-time monitoring and judgment of the slurry's transition from a flow state to a solidification state at the construction site. For example, when the length of the abandoned pipeline is long (e.g., more than 500 meters), the second preset time can be set to 20 minutes. This means that the first state check is performed 20 minutes after the slurry enters the pipeline. If the slurry still has good fluidity at this time, it indicates that the current slurry mixing ratio, de-adhesive dosage, and mixing process parameters are suitable for long-distance transportation. Conversely, the mixing process or de-adhesive dosage can be adjusted in time to prevent premature solidification and pipeline blockage. When the length of the abandoned pipeline is short (e.g., 100 to 200 meters), the second preset time can be shortened to about 10 minutes to quickly determine whether the slurry has suitable fluidity and a suitable solidification time under short-distance transportation conditions. This prevents the slurry from failing to solidify for a long time or solidifying too quickly, ensuring that the slurry always meets the expected construction requirements.

[0068] Specifically, the deviscosifying agent solution is used to remove the high viscosity of the purified water residue slurry and improve the fluidity of the solidified residue slurry.

[0069] As mentioned above, besides sodium citrate solution, other types of low-cost, environmentally friendly deblocking agents can be considered, such as natural polymers (e.g., chitosan) or inorganic salts (e.g., calcium chloride, sodium sulfate). These novel deblocking agents can work synergistically with sodium citrate solution to jointly exert a deblocking effect, while controlling the viscosity of the mud, avoiding excessive costs or environmental burden caused by the overuse of a single deblocking agent. For example, natural polymers form molecular chains in the solution, which can effectively reduce the internal friction of the mud, making the mud more uniform during stirring, reducing clumping and agglomeration, and thus enhancing fluidity.

[0070] The proportion of the de-adhesive solution should not be fixed, but rather adjusted in real time according to the viscosity and moisture content of the residual sludge. By incorporating an online monitoring system, the viscosity and fluidity of the sludge can be monitored in real time, and the amount of de-adhesive added can be automatically adjusted. When the viscosity of the sludge is high (e.g., when the moisture content of the residual sludge is low), the proportion of the de-adhesive solution can be increased to ensure good fluidity of the sludge; while when the viscosity is low (e.g., when the moisture content of the residual sludge is high), the amount of de-adhesive added should be reduced to avoid excessive de-adhesive causing the sludge to become too fluid, thereby ensuring the stability of the solidification effect.

[0071] To improve the efficiency of deblocking agent solutions and reduce dosage, targeted release technology can be employed. This involves designing a slow-release formulation for the deblocking agent solution, allowing it to gradually release its effects upon contact with the purified sludge slurry. This can be achieved by combining the deblocking agent with a carrier material (such as ultrafine powder, natural polymers, or hydrogels) to control the release rate, resulting in a more uniform and continuous deblocking process. This maintains the fluidity of the slurry for a longer period, preventing premature failure.

[0072] By introducing cross-linking technology into the de-adhesive solution, a three-dimensional network structure is formed after the de-adhesive solution is added to the purified water and residual mud slurry. This cross-linked structure allows for better control of the distribution of the de-adhesive solution, preventing excessively rapid dissolution or diffusion, while maintaining a continuous de-adhesive effect on highly viscous substances. During the curing process, the cross-linked network structure effectively disperses solid particles in the mud, enhancing fluidity and making the flowed and cured residual mud slurry more uniform and stable in subsequent operations, thus improving the smoothness of the construction process.

[0073] Furthermore, in the self-leveling filler material of the present invention, based on the total mass of wet soil containing residual sludge and clean water, the mass percentage of slag powder is 0-10%, such as 0%, 5%, 10%, preferably 10%; the mass percentage of cement is 10%-20%, such as 10%, 15%, 20%, preferably 15%; the mass percentage of sodium citrate is 1%-2%, such as 1%, 1.5%, 1.75%, 2%, preferably 1.75%; and the mass percentage of water is 16.7%.

[0074] The slag powder used in the following embodiments of the present invention is S95 grade finely ground blast furnace slag powder, and its chemical composition is shown in Table 1. The cement used is pozzolanic silicate PP32.5 cement powder, and its chemical composition is shown in Table 2. The residual sludge used is undisturbed wet soil produced by the water plant, and its basic physical properties and chemical composition are shown in Tables 3 and 4.

[0075] Table 1 Chemical composition of slag powder

[0076]

[0077] Table 2 Chemical composition of PP325 cement

[0078]

[0079] Table 3 Basic Physical Properties of Residual Sludge from Water Purification

[0080]

[0081] Table 4 Chemical composition of waste sludge from water purification

[0082]

[0083] In any of the above embodiments, a deblocking agent formulation was designed. Based on the total mass of the deblocking agent, the mass ratio of sodium citrate was 6%-12%, and the mass ratio of water was 88%-94%. A total of four deblocking agent formulations were designed, as shown in Table 5. Sodium citrate was dissolved in water according to the deblocking agent formulation to obtain the flocculant.

[0084] Table 5 Detachable Agent Proportions

[0085]

[0086] In this embodiment, the descaling agent liquid prepared according to each proportion is mixed with the purified water and residual mud, and then placed in a planetary mixer and stirred for 4 minutes to obtain the purified water and residual mud slurry.

[0087] In any of the above embodiments, the self-leveling filler material was prepared using the above-mentioned de-adhesive ratio. Based on the wet soil quality of the original clean water residue, the curing agent was mixed with the clean water residue slurry at a mass ratio of 20%-25%, and stirred for 10 minutes using a planetary mixer to obtain a flowable and cured residue self-leveling filler material. The flow properties and unconfined compressive strength at 28 days were tested, and a comparison was made using pure cement as the curing agent. The test results are shown in Table 6.

[0088] Table 6 Flowability and Strength (Sodium Citrate)

[0089]

[0090]

[0091] The test results in Table 6 show that the curing agent prepared using "cement + slag powder" has a good flow curing effect on the waste sludge. With the action of a deblocking agent containing 1% sodium citrate, the unconfined compressive strength of the flow-cured waste sludge at 28 days is 26.67 kPa when the curing agent content is 25%. As the sodium citrate content increases, the strength decreases; for example, when the sodium citrate content is 2% and the curing agent content is 25%, the strength at 28 days is only 6.67 kPa, but its flowability is greatly improved. Compared with cement curing agents, the unconfined compressive strength of the flow-cured waste sludge at 28 days is lower than that of cement-cured waste sludge, but the important indicator of "flowability" of the flow-cured waste sludge is superior to that of cement-cured waste sludge. Under the action of a detackifier with 1.75% sodium citrate, the flow value of the solidified sludge was 23.1%, 11.2%, and 4.7% higher than that of the cement solidified body as the cement content increased.

[0092] The curing agent prepared by "cement + slag powder" exhibits good flow and curing effect on the residual sludge of clean water under the action of the de-adhesive, which can largely meet the flow performance and strength requirements of urban underground abandoned pipe filling projects.

[0093] In any of the above embodiments, the viscosity of the system using sodium citrate as the main desiccant can be effectively reduced by the purification of residual sludge, greatly improving its flowability. Based on the experimental data in Table 6, ferrous sulfate with strong redox effects was added for optimization, and a self-leveling filler material was prepared. Similarly, based on the wet soil mass of the original purified residual sludge, the curing agent was mixed with the purified residual sludge slurry at a mass dosage of 20%-25%, and stirred for 10 minutes using a planetary mixer to obtain a flowable and solidified residual sludge self-leveling filler material. The initial flowability and unconfined compressive strength at 28 days were tested, and cement was used as a comparison. The test results are shown in Table 7.

[0094] Table 7 Flowability and Strength (Ferrous Sulfate)

[0095]

[0096]

[0097] An embodiment of the third aspect of the present invention provides an application method for self-leveling filling of waste pipe material implemented through any of the above embodiments. In some embodiments of the present invention, such as Figs. 2-3 As shown, the application method includes the following steps:

[0098] S201, place a mixing tank on the ground, and excavate soil above the underground abandoned pipe to be treated to form a through grouting hole.

[0099] S202 connects the mixing tank and grouting pump to the grouting hole of the underground abandoned pipeline through the grout delivery pipe.

[0100] S203, in a mixing tank, the composite powder and de-adhesive solution are mixed with the purified water residue to obtain a flowable solidified residue slurry.

[0101] S204 involves pumping the solidified residual mud slurry into an underground abandoned pipeline using a grouting pump and a grout delivery pipe, and repeating the pumping process until the abandoned pipeline is filled with slurry.

[0102] This invention proposes an application method that involves excavating earth above the location of an underground abandoned pipeline to form a continuous grouting hole. The key to this operation is ensuring a smooth connection between the grouting hole and the abandoned pipeline, allowing the grout to be smoothly injected into the pipeline. Typically, the grouting hole needs to be of sufficient size to ensure uniform distribution of the grout inside the pipeline and achieve the desired filling effect. Furthermore, during excavation, care must be taken to protect other structures of the underground pipeline to avoid unnecessary damage. The continuity and precise positioning of the grouting hole ensure the smooth implementation of subsequent steps. A mixing tank is used to prepare the fluidized solidified slurry, while a grouting pump is responsible for delivering the prepared slurry into the abandoned pipeline. Connecting the mixing tank, grouting pump, and grout delivery pipe ensures the normal operation of all equipment, enabling efficient and continuous grouting operations. The design of the grout delivery pipe must meet the fluidity requirements of the fluidized solidified slurry to avoid blockages or other obstructions during delivery. In this process, the selection of the grouting pump is particularly critical. The grouting pump needs to have sufficient pumping capacity to ensure that the flowable solidified slurry can be stably and continuously delivered into the abandoned pipeline. The composite powder and de-adhesive solution are added to the purified slurry in a mixing tank for mixing. The composite powder's role is to solidify the purified slurry, ensuring its stability within the pipeline and preventing slurry separation or deformation due to changes in the pipeline environment. The de-adhesive solution is used to reduce the high viscosity of the purified slurry, making the mixed slurry more fluid and easier to deliver into the pipeline by the grouting pump. Furthermore, the mixing process in the mixing tank needs to maintain uniformity to ensure that the composite powder, purified slurry, and de-adhesive solution are fully integrated, avoiding uneven slurry composition or insufficient fluidity. Using a high-efficiency planetary mixer ensures effective mixing and prevents uneven distribution or agglomeration of solid particles in the slurry. The mixed flowable solidified slurry is then transported to the abandoned pipeline through a grouting pipe using the grouting pump. The pumping action of the grouting pump allows the grout to flow smoothly into the pipeline, filling its internal voids and ensuring a complete and uniform filling. Because abandoned pipelines may have complex internal structures or bends, the grouting process requires repeated pumping to ensure the grout is evenly distributed and covers every corner of the pipeline. Especially for longer abandoned pipelines, repeated pumping effectively prevents grout stratification or uneven flow due to long transport distances. After multiple grouting sessions, the abandoned pipeline is completely filled, ensuring its stability and integrity. This iterative process ensures uniform grout distribution within the pipeline, not only filling voids but also providing a degree of sealing to prevent future environmental pollution or leakage within the abandoned pipeline.

[0103] In the description of this invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this invention, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.

[0104] The above embodiments are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing a self-leveling filler for waste pipes, characterized in that, This method is used to treat residual sludge from wastewater filtration and purification processes. The residual sludge is in the form of a highly viscous slurry, and its components include at least one of silica, alumina, iron oxide, potassium oxide, titanium dioxide, phosphorus pentoxide, magnesium oxide, and calcium oxide. The preparation method includes the following steps: S101, Obtain the purified water residue produced by the purified equipment for treating wastewater, and configure the total mass of composite powder and the total mass of deblocking agent solution based on the total mass of the purified water residue; S102, the de-adhesive solution is mixed into the clean water and residual mud in the mixing pot, and the clean water and residual mud slurry is obtained by mixing with a mortar planetary mixer. S103, the composite powder is prepared by mixing cement powder and slag powder, the composite powder is added to the purified water residue slurry, and a planetary mixer is used to perform mixing for a first preset time to form a fluidized solidified residue slurry; wherein, the composite powder is used to control the fluidity retention time of the purified water residue slurry before solidification; and the first preset time is set according to the mass ratio of the slag powder to the cement powder. The deviscosifying agent solution is used to remove the high viscosity of the purified water residue slurry and improve the fluidity of the solidified residue slurry.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the slag powder to the cement powder in the composite powder is between 0.1 and 1.

3. The preparation method according to claim 2, characterized in that, Before the cement powder comes into contact with the purified water residue slurry, the slag powder is mixed with the cement powder to form an isolation layer between the cement powder particles.

4. A self-leveling filler for waste pipes produced by the preparation method according to any one of claims 1-3, characterized in that, The mass ratio of the composite powder to the residual sludge from the water treatment process is between 0.20 and 0.

30. The mass ratio of the descaling agent solution to the residual sludge from the water treatment is between 0.17 and 0.

19.

5. The self-leveling filler for waste pipes according to claim 4, characterized in that, The slag powder comprises at least one of the following: calcium oxide, silicon dioxide, sulfur trioxide, aluminum oxide, iron oxide, magnesium oxide, sodium oxide, and potassium oxide.

6. The self-leveling filler for waste pipes according to claim 4, characterized in that, The cement powder comprises at least one of calcium oxide, silicon dioxide, aluminum oxide, iron oxide, magnesium oxide, sulfur trioxide, potassium oxide, and titanium dioxide.

7. The self-leveling filler for waste pipes according to claim 4, characterized in that, The de-adhesive solution includes a sodium citrate solution; the sodium citrate in the sodium citrate solution accounts for 6 to 12 parts by mass, and the water in the sodium citrate solution accounts for 88 to 94 parts by mass.

8. A method for applying a self-leveling filler material for waste pipes produced by the preparation method according to any one of claims 1-3, characterized in that, Includes the following steps: Place a mixing tank on the ground and excavate soil above the underground abandoned pipes to be treated to form a through grouting hole; The mixing tank and grouting pump are connected to the grouting hole of the underground abandoned pipeline through a grout delivery pipe; In the mixing tank, the composite powder and the de-adhesive solution are mixed and stirred with the purified water residue to obtain the flowable solidified residue slurry; The fluidized solidified slurry is pumped into an underground abandoned pipeline using a grouting pump and a grout delivery pipe. The slurry is repeatedly pumped in until the abandoned pipeline is filled with slurry.

Citation Information

Patent Citations

  • Method for preparing controllable low-strength material from sludge in waterworks, and material

    CN111499280A

  • Micro-expansion water purification sludge alkali-activated grouting material for backfilling urban waste underground pipelines and preparation method of micro-expansion water purification sludge alkali-activated grouting material

    CN118878296A